Good Intentions are not enough: United States Foreign Policy Toward Latin America in the Twentieth Century - Barreto Velázquez, Norberto (2019)
This essay examines the US government’s attempts throughout the 20th century to improve its relations with Latin America. It shows that most of these efforts were motivated by external factors such as wars or conflicts with other world powers. Although genuine, these attempts were ultimately subordinate to the United States’ geopolitical and economic foreign policy priorities. Racial elements and, especially, the ignorance of US policymakers dedicated to Latin American affairs, played a role in limiting the success of US initiatives. The essay concludes that a world power’s good intentions alone do not qualify as behaving like a good neighbor.